Factors Influencing Farmers Purchase Intention toward Insecticides of Rajkot District, India - , Y. H. Oganja; , H. Y. Maheta; , Kalpesh Kumar; , C. R. Bharodia (Archives of Current Research International, 2024)
The present study was conducted to identify the factors influencing farmers purchase intention toward insecticide of Rajkot district. A multi-stage random sampling method was used to select the samples during the actual survey. Total 120 insecticide users were selected randomly from Rajkot district. Principal component analysis was used to identify the factors influencing farmers purchase intention towards insecticide of Rajkot district. The result revealed that six components were product performance, financial support, product specifications, sales team influence, feedback and social influence, significantly impact farmers' purchase intentions for insecticides. The study concludes that multiple factors, including Product performance and farmer experience are the most influential, indicating the importance of reliable and effective products.